Effects of Exercise Protocol on the Estimation of Anaerobic Threshold Based on Heart Rate-Work Rate Relationships - Özçelik, Oğuz; Ayar, Hakkı (Fırat University, 2004)
Aim: We investigated the effects of work different work load increments on the validity of non-invasive aerobic to anaerobic metabolic transition point estimation from heart rate-work rate relationships during incremental exercise tests. Material and Method: Thirteen male subjects (21.0±0.4 yr) performed two incremental exercise tests with work rates of 15 W/min (W15) and 30 W/min (W30) until the limit of tolerance using an electromagnetically-braked cycle ergometer. During exercise, heart rate was measured using polar heart rate watch; respiratory parameters were estimated using spirometry. Aerobic to anaerobic metabolic transition point estimated from ventilation to work rate relationships and compared with heart rate-work rate relationship. Results: We have found three different responses in heart rate-work rate relationships during incremental exercise test. A linear relationships observed in 6 (W15) and 7 (W30) subjects. Heart rate-work rate relationship showed a deflection to left side in 2 (W15) and 4 (W30) subjects and a right side deflection in 5 (W15) and 2 (W30) subjects. There was no an association between aerobic to anaerobic metabolic transition point and heart rate-work rate deflection point only in any subjects. Conclusion: Consequently, heart rate-work rate deflection point may not provide accurate aerobic to anaerobic metabolic transition point estimation. The different work protocols may also lead changes in heart rate–work rate relationships. Thus, investigators or clinicians should be careful using heart rate deflection point.

Amaç: Farklı egzersiz protokollerinin kalp atım hızı-iş gücü arasındaki ilişki ile aerobik-anaerobik metabolizma değişim bölgesinin non-invazif olarak tespit edilmesindeki etkinliği araştırıldı. Gereç ve Yöntem: On üç erkek denek (21.0±0.4 yıl) elektro manyetik bisiklet ergometre ile protokolleri 15 (W15) W/dk ve 30 W/dk (W30) olarak artan yüke karşı yapılan egzersiz testlerine katıldılar. Egzersiz sırasında, kalp atım hızları polar kalp saati ile, solunum parametreleri ise spirometre ile ölçülüp değerlendirildi. Aerobik-anaerobik metabolizma değişim bölgesi, solunum-iş gücü ilişkisi ile hesaplandı ve kalp atım hızı-iş gücü ile karşılaştırırldı. Bulgular: Egzersiz sırasında kalp atım hızı-iş gücü arasında ilişki 3 farklı şekilde gözlendi. Kalp atım hızı artan iş gücü ile lineer olarak 6 (W15) ve 7 (W30) artma gösterdi. Kalp atım hızında sola kırılma 2 (W15) ve 4 (W30) denekte, sağa kırılma ise 5 (W15) ve 2 (W30) denekte gözlendi. Aerobikanaerobik metabolizma değişim bölgesi ile kalp atım hızı kırılma noktası deneklerin hiçbirinde gözlenmedi. Sonuç: Kalp atım hızı kırılma noktası aerobik-anaerobik metabolizma değişim bölgesi hesaplanmasında etkin bir sonuç vermemektedir. Uygulanan egzersiz protokolü ise kalp atım kırılım yönlerinde kısmi değişikliklere neden olmaktadır. Bu nedenle kalp atım hızı iş gücü ilişkisi ileri çalışmalara ihtiyaç duymakta ve klinik alanda antrenman veya egzersiz programlarının hazırlanmasında uygulanırken dikkat edilmelidir.
Egzersiz Protokolünün Kalp Atım Hızı–İş Gücü İlişkisine Dayanan Anaerobik Eşik Hesaplanmasına Etkisi